2020
DOI: 10.1101/2020.02.03.932053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survival strategies ofEnterococcus mundtiiin the gut ofSpodoptera littoralis: a live report

Abstract: 21The complex interaction between a higher organism and its resident gut flora is a subject of 22 immense interest in the field of symbiosis. Many insects harbor a complex community of 23 microorganisms in their gut. Larvae of Spodoptera littoralis, a lepidopteran pest which is 24 prevalent in tropical and subtropical regions of the world, have a tube-like gut structure 25 containing a simple bacterial community. This community varies both spatially (along the 26 length of the gut) and temporally (during the l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…E. mundtii with adherence properties can form a biofilm layer on the gut wall to help insect adapt to altered environments ( Mazumdar et al., 2021b ). Probiotic characterization of E. mundtii was observed from larval gut of Plutella xylostella ( Mazumdar et al., 2021a ). Members of other gut microbiomes can also degrade insecticides in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…E. mundtii with adherence properties can form a biofilm layer on the gut wall to help insect adapt to altered environments ( Mazumdar et al., 2021b ). Probiotic characterization of E. mundtii was observed from larval gut of Plutella xylostella ( Mazumdar et al., 2021a ). Members of other gut microbiomes can also degrade insecticides in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that Enterococcus is the most prevalent and abundant group identified in the gut microbiota of Spodoptera species [78, 79, 83], and also the most active in the gut of S. frugiperda [84]. Additionally, it has been demonstrated that Enterococcus mundtii is effective in colonizing and forming biofilm in the gut of Spodoptera littoralis [22, 27]. There is also evidence that E. mundtii can be inherited by S. littoralis through vertical transmission [23].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the high variation in the composition of the microbial community driven by host plants would difficult the occurrence of associations that could hold through the required evolutionary time in order to allow the selection and establishment of true gut residents [21]. Nevertheless, other studies have shown that even in hostile environments as the midgut of lepidopteran larvae, there are evidence of gut colonization by certain bacterial groups [2224]. In addition, gut-resident bacteria of lepidopteran larvae were demonstrated to play important physiological roles for their hosts [25, 26]; besides, the continuous association with their hosts for some of these microbes has been proved as they are horizontally transmitted [27].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the high variation in the composition of the microbial community driven by host plants would difficult the occurrence of associations that could hold through the required evolutionary time in order to allow the selection and establishment of true gut residents . Nevertheless, other studies have shown that even in hostile environments as the midgut of lepidopteran larvae, there are evidence of gut colonization by certain bacterial groups Mazumdar et al, 2020;. In addition, gut-resident bacteria of lepidopteran larvae were demonstrated to play important physiological roles for their hosts (Yongqi Shao, Arias-Cordero, Guo, Bartram, & Boland, 2014;Xia, Lan, Tao, Lin, & You, 2020); besides, the continuous association with their hosts for some of these microbes has been proved as they are horizontally transmitted (Y. .…”
Section: Introductionmentioning
confidence: 99%